2000
DOI: 10.1097/00063198-200001000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory viruses and asthma

Abstract: Viral infections have become increasingly recognized as a significant cause of asthma exacerbations, mainly because of improved viral detection techniques. Unfortunately, the ability to specifically treat viral infections and to limit the asthma morbidity associated with these agents has not kept pace with diagnostic technology. This article focuses on current concepts of the epidemiology of viruses in asthma exacerbations, investigations studying the physiologic and immunologic consequences of viral infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…43, 44 It is conceivable that the downregulation of STAT1 phosphorylation in severe allergic asthmatic patients might render them more susceptible to certain infections. Although we have shown that STAT1 signaling was impaired in all memory CD4 + T cells of allergic asthmatic patients, an actual link between the downregulation of STAT1 phosphorylation and susceptibility to atypical mycobacterial or viral respiratory infection requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…43, 44 It is conceivable that the downregulation of STAT1 phosphorylation in severe allergic asthmatic patients might render them more susceptible to certain infections. Although we have shown that STAT1 signaling was impaired in all memory CD4 + T cells of allergic asthmatic patients, an actual link between the downregulation of STAT1 phosphorylation and susceptibility to atypical mycobacterial or viral respiratory infection requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…12,17 We have argued that RRVD is caused by immunopathologic inflammatory responses directed at virus persisting in synovial macrophages. 1,18 -20 A number of virusmediated immune pathologies are currently treated with steroids; these include croup in children, 21 virus-induced asthma flares, 22 Bell palsy, 23 viral encephalitis, 24 and hepatitis C virus arthritis. 25 Although RRVD can be severe and debilitating at onset, the disease progressively resolves within 3 to 6 months, there is no discernible articular damage, and there is no evidence of RRVD leading to autoimmune arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the serotype of RV involved may be important and some strains such as RV16 are particularly associated with reduced lung function and increased AHR and symptoms of asthma and rhinitis (Peebles & Hartert, 2000).…”
Section: Decreased Lung Function/ahr Several Investigatorsmentioning
confidence: 99%